Size‐Dependent Consequences of Exogenous Cortisol Manipulation on Overwinter Survival and Condition of Largemouth Bass. Issue 1 (23rd February 2017) - Midwood, Jonathan D.; Peiman, Kathryn S.; Burt, Aja E.W.; Sarker, Mohammed Yusuf; Nannini, Michael A.; Wahl, David H.; Cooke, Steven J.
GRAPHICAL ABSTRACT: We found no evidence of a size‐dependent response to stress in a wild teleost fish, but some evidence for sex‐specific changes in condition and health metrics. ABSTRACT: Little is known about the size‐dependent consequences of stressors on wild animals, which is particularly relevant during winter where size‐specific trends in survival are common. Here, exogenous cortisol manipulation was used to investigate the effect of a physiological challenge on overwinter mortality and spring condition of largemouth bass ( Micropterus salmoides ) across a range of body sizes. Fish were wild‐caught in the fall, assigned into either control or cortisol manipulated treatments, and held in replicated experimental ponds. For bass that survived the winter, length, mass, and health metrics (e.g., gonadosomatic index [GSI], hepatosomatic index [HSI], and water content) were determined in the spring. Winter survival was marginally lower for cortisol treated bass; however, there was no influence of initial length, mass, or condition on overwinter survival. When bass were grouped by size, survival was significantly higher for bass 300–350 mm in length compared to those <200 mm. The treatment did not strongly influence spring health metrics, suggesting that largemouth bass that survived the winter were able to recover from the effects of the cortisol elevation. Initial size and sex were linked to some spring health metrics, with large females having the highest GSI and HSI scores. Overall, results from this study do not support the notion that there are size‐dependent responses to cortisol manipulation in a teleost fish. Rather, this type of physiological challenge may modulate the natural rates of winter mortality that are primarily driven by starvation and predation, independent of body size, in subadult and adult largemouth bass.